1998
DOI: 10.1016/s0735-1097(98)00136-3
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is a Potent Predictor of Mortality Independently of and in Combination With Troponin T in Acute Coronary Syndromes: A TIMI 11A Substudy

Abstract: Elevated CRP at presentation in patients with unstable angina or NQMI is correlated with increased 14-day mortality, even in patients with a negative rapid cTnT assay. Quantitative CRP and a rapid cTnT assay provide complementary information for stratifying patients with regard to mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
359
1
35

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 716 publications
(413 citation statements)
references
References 37 publications
18
359
1
35
Order By: Relevance
“…The present study confirms previous observations that levels of CRP and MPO are elevated during ACS, 4,6,7,9 suggesting the participation of these proteins in the pathophysiologic process. After 2.4 y of follow-up, these markers significantly decreased with the stabilization of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirms previous observations that levels of CRP and MPO are elevated during ACS, 4,6,7,9 suggesting the participation of these proteins in the pathophysiologic process. After 2.4 y of follow-up, these markers significantly decreased with the stabilization of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…1 -3 Much data exist on the prognostic capacity of C-reactive protein (CRP) determined in patients with acute coronary syndrome (ACS). 4 Some, but not all, studies have demonstrated an association between CRP levels and increased mortality. 5 -8 A novel inflammatory marker, myeloperoxidase, released by neutrophils activation, has also shown potential for risk stratification in ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…High-sensitivity C-reactive protein (CRP), a marker of inflammation, has been identified as an independent predictor of adverse cardiac events in healthy populations and in patients with stable coronary artery disease or ACS (6)(7)(8)(9)(10)(11). Although it is clear that inflammation plays a role in atherosclerotic complications (12), the relationship between CRP and troponin release following PCI has not been clarified.…”
mentioning
confidence: 99%
“…14 Elevated C-reactive protein (CRP) levels have been shown to be associated with ACS. 15,16 CRP levels reflect the intensity of an inflammatory process involving macrophages, T and B cells, immunoglobulin (Ig) G deposition, and M-CSF production. CRP has a proinflammatory effect on endothelial cells and VSMCs.…”
mentioning
confidence: 99%